Mislabeling, illegal capture, and commercialization of Atlantic goliath grouper (Epinephelus itajara) on the Brazilian coast using DNA barcoding - Lorena Lopes Almeida; Maurício Hostim-Silva; Mario Vinícius Condini; Matheus Oliveira Freitas; Leonardo Schlögel Bueno; Bianca Bentes; Luciano de Jesus Gomes Pereira; Ana Paula Cazerta Farro (Neotropical Ichthyology, 2024)
Abstract The Atlantic goliath grouper Epinephelus itajara is the largest grouper species in the Atlantic Ocean. Despite the conservation status being Vulnerable (VU) globally and Critically Endangered (CR) in Brazil, the species continues to face threats from overfishing throughout its range. We used DNA barcoding employing the mitochondrial Cytochrome c oxidase subunit I (COI) gene to identify the illegal commercialization of E. itajara in fish markets from the northern (NC) and southern (SC) Brazilian coasts. Sampling was conducted in fish markets and aimed to confirm the identification of mischaracterized fish sold as E. itajara in the NC, as well as identifying fish fillets sold as the Dusky grouper in the SC. DNA barcoding allowed the unambiguous identification of 22 (84.6%) of the 26 analyzed fish market samples. Both sampled areas had confirmation of E. itajara illegal commercialization and from the 22 analyzed samples, 17 (77.3%) were confirmed to be E. itajara. Here we report two crimes, the illegal sale of E. itajara and commercial fraud by species substitution. This study has highlighted that the existing legislation that protects E. itajara in Brazilian waters requires the adoption of better public policies for the conservation of the species.